1350 Wide-Awake Local Anaesthetic No Tourniquet (WALANT) Vs General/Regional Anaesthetic for Flexor Tendon Injuries: A Single-Centre, Retrospective Cohort Study. (12th October 2021) - Greasley, L; Patel, P; Nolan, G; Bamal, R; Bell, D
Abstract: Aim: Flexor tendon repairs are commonly performed under general/regional anaesthesia. Wide-awake local anaesthetic no tourniquet (WALANT) has potential advantages including the ability to test the repair intra-operatively; removal of the risks of general anaesthesia; no aerosol generation, thus reducing COVID-19 transmission risk. An ongoing systematic review identified no comparative studies. This study aimed to compare the functional outcomes and complications of flexor tendon repairs under WALANT and general/regional anaesthetic. Method: A single-centre, retrospective cohort study was undertaken (July 2019-August 2020). Consecutive adult patients undergoing flexor tendon repair were included. Exclusion criteria were ≥ 3 injured fingers; concurrent hand fracture; revascularisation; replantation. Data were collected on demographics, injuries, operative technique, and outcomes. Results: Overall, 139 patients with 165 injured digits were included. Most (60%) were repaired under general anaesthesia. Local anaesthetic (was used for 46 patients (21 with tourniquet, 25 WALANT). Only 30% (42/139) patients had range of motion data at 6-weeks, dropping to 19% (26/139) at 12-weeks. WALANT patients had fewer ruptures (8% vs 14%), fewer adhesions requiring tenolysis (0% vs 4%) and less complications overall than the general/regional anaesthesia group. The results were not found to be statistically significant. Conclusions: The lack of data due to patients not attending follow-up, makes meaningful research on flexor tendon injuries very challenging. This study suggests WALANT may reduce complications but is limited by the inherent bias of a retrospective, non-randomised study, and small numbers. Adequately designed and powered studies are recommended in future to further investigate the potential benefits of wide-awake surgery.